Preparation method of cellulose / nano-zinc oxide composite aerogel

By modifying nano zinc oxide and lyophilizing with cellulose, a cellulose/nano zinc oxide composite aerogel was prepared, which solved the insufficient mechanical strength of the cellulose aerogel, complex preparation process, high cost and hygroscopicity of the cellulose aerogel. Problems such as excessive height have achieved more efficient thermal insulation performance.

CN119431875AActive Publication Date: 2025-02-14JIANGNAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411714988.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-14
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Cellulose aerogels have defects such as insufficient mechanical strength, complex preparation process, high cost and high hygroscopicity in thermal insulation applications.

Method used

By modifying nano zinc oxide, the cellulose solution and modified nano zinc oxide are directionally frozen to obtain a cellulose/nano zinc oxide composite hydrogel, and then freeze in liquid nitrogen and vacuum freeze drying to prepare fibers Cin/nano zinc oxide composite aerogel.

Benefits of technology

The mechanical performance of cellulose aerogel is improved, the preparation process is simplified, the cost is reduced and the hygroscopicity is reduced, which has significantly improved its application performance in the field of thermal insulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431875A_ABST
    Figure CN119431875A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of cellulose / nano-zinc oxide composite aerogel, and belongs to the field of functional materials. The preparation method comprises the following steps: modifying nano zinc oxide with a silane coupling agent, and dissolving cellulose in a pre-cooled aqueous solution of sodium hydroxide and urea to obtain a cellulose solution; adding the modified nano-zinc oxide particles into a cellulose solution in a stirring state to obtain a cellulose / nano-zinc oxide mixed solution, then performing directional freezing, replacing the formed gel with ethanol, and washing with deionized water to remove redundant solvent until the pH value is equal to 7 to obtain the cellulose / nano-zinc oxide composite hydrogel. And drying in a freeze dryer to obtain the cellulose / nano-zinc oxide composite aerogel. The interior of the prepared aerogel has an orderly-arranged directional pore structure, and the aerogel has the advantages of being good in mechanical property, hydrophobic property and heat-insulating property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional materials, specifically relating to a method for preparing cellulose / nano zinc oxide composite aerogel. Background Art

[0002] Thermal insulation materials play a vital role in modern architecture and industry. With the continuous growth of global energy demand and increasing environmental awareness, high-efficiency insulation materials have become a key means of reducing energy consumption and carbon emissions. In the field of insulation materials, petroleum-based foam plastics such as polyurethane, expanded polystyrene, and mineral wool are widely used due to their excellent insulation performance. However, these materials have drawbacks such as high flammability, non-renewability, and non-biodegradability, leading to increasingly serious waste pollution problems and hindering their sustainable development. In contrast, cellulose aerogels possess high porosity, low density, large adsorption capacity, excellent thermal insulation performance, and natural environmental sustainability. These characteristics make them highly promising for applications in multiple fields such as adsorption, insulation, and energy storage. The air-filled pores and extremely low thermal conductivity of cellulose aerogels effectively hinder heat conduction and convection, giving them superior thermal insulation capabilities.

[0003] Cellulose aerogels still face several challenges in practical applications. First, their mechanical properties are insufficient, lacking adequate toughness and compressive strength, making them prone to collapse under external forces. Second, the abundance of hydrophilic hydroxyl groups in the cellulose molecular chain makes cellulose aerogels highly hygroscopic in high-humidity environments, leading to increased total thermal conductivity and decreased insulation performance. These mechanical deficiencies and high hygroscopicity significantly limit the widespread application of cellulose aerogels in thermal insulation. After cellulose is regenerated or non-regenerated to form a stable gel system, further drying processes are required to replace the liquid phase component in the gel with air to obtain the aerogel. Traditional aerogel drying methods, such as atmospheric pressure drying and supercritical drying, often suffer from complex processes, high costs, and unstable aerogel structures, limiting their large-scale application. Summary of the Invention

[0004] [Technical Issues]

[0005] The technical problem to be solved by this invention is that cellulose aerogel has defects such as insufficient mechanical strength, complex preparation process, high cost and excessive moisture absorption in thermal insulation applications.

[0006] [Technical solution]

[0007] To address the aforementioned problems, this invention provides a method for preparing a cellulose / nano zinc oxide composite aerogel thermal insulation material. Using cellulose as a raw material, nano zinc oxide is modified, and a cellulose solution and modified nano zinc oxide are directionally frozen to obtain a cellulose / nano zinc oxide composite hydrogel. This hydrogel is then frozen in liquid nitrogen and transferred to a vacuum freeze dryer for drying, yielding a cellulose / nano zinc oxide composite aerogel. This method is low-cost, simple, and allows for controllable aerogel structure.

[0008] This invention provides a method for preparing a cellulose / nano zinc oxide composite aerogel thermal insulation material, specifically including the following steps:

[0009] (1) Add nano zinc oxide to anhydrous ethanol, stir ultrasonically to obtain nano zinc oxide suspension, add γ-methacryloxypropyltrimethoxysilane to the suspension for reaction, and finally centrifuge, wash and dry to obtain modified nano zinc oxide particles.

[0010] (2) Add sodium hydroxide and urea to water, stir until dissolved, then pre-freeze to obtain pre-cooled alkaline solution. Then add cellulose to the pre-cooled alkaline solution, stir to react, and obtain cellulose solution.

[0011] (3) Add the modified nano zinc oxide particles to the cellulose solution and stir to mix them to obtain a cellulose / nano zinc oxide mixed solution;

[0012] (4) After the cellulose / nano zinc oxide mixed solution is placed in a directional freezing device for treatment, it is taken out and allowed to stand, and then washed to obtain cellulose / nano zinc oxide composite hydrogel.

[0013] (5) The cellulose / nano zinc oxide composite hydrogel was freeze-dried to obtain cellulose / nano zinc oxide composite aerogel.

[0014] In one embodiment of the present invention, in step (1), the mass ratio of nano zinc oxide to anhydrous ethanol is 1:20-30.

[0015] In one embodiment of the present invention, in step (1), the mass ratio of nano zinc oxide to γ-methacryloxypropyltrimethoxysilane is 10-20:1.

[0016] In one embodiment of the present invention, in step (1), the reaction temperature is 80-100℃ and the reaction time is 10-12h.

[0017] In one embodiment of the present invention, in step (2), the mass ratio of sodium hydroxide, urea, water and cellulose is 7:26:67:3.

[0018] In one embodiment of the present invention, in step (2), the pre-freezing temperature is -18 to -12°C and the pre-freezing time is 3 to 5 hours.

[0019] In one embodiment of the present invention, in step (2), cellulose is added to a pre-cooled alkaline solution and stirred at 1-3°C for 3-5 hours.

[0020] In one embodiment of the present invention, in step (3), the mass ratio of modified nano zinc oxide particles to cellulose is 1:(5-10), and the stirring time is 1-3h.

[0021] In one embodiment of the present invention, in step (4), the directional freezing temperature is -196°C and the time is 20-30 min.

[0022] In one embodiment of the present invention, in step (4), the mixture is left to stand at room temperature for 5-8 hours.

[0023] In one embodiment of the present invention, in step (5), the freeze-drying temperature is -55°C and the time is 24-48h.

[0024] This invention provides a cellulose / nano zinc oxide composite aerogel prepared by the method described above.

[0025] This invention provides the application of the cellulose / nano zinc oxide composite aerogel described above in the field of thermal insulation materials.

[0026] Beneficial effects:

[0027] (1) This invention constructs a stable organic modified layer on the surface of nano-zinc oxide by grafting modification of nano-zinc oxide particles. This reduces the attraction and aggregation tendency between particles, prevents precipitation or aggregation in the matrix, and achieves uniform dispersion of nano-zinc oxide.

[0028] (2) NaOH-urea solution, as a non-derivative solvent for cellulose, exhibits enhanced hydrogen bond breaking ability, especially at low temperatures. This allows urea to more effectively disrupt the hydrogen bonds between cellulose molecules, thus promoting solvent-cellulose interaction and efficient cellulose dissolution. Simultaneously, the low temperature helps maintain solution stability and prevents cellulose recrystallization and precipitation. Under sustained low-temperature conditions, the outer layer of cellulose dissolves first, and the viscosity of the dissolved cellulose gradually increases slowly at low temperatures. Subsequently, urea and NaOH diffuse into the cellulose core, completely dissolving the cellulose. Compared to the expensive solvents and processing agents used in traditional methods, the low-temperature sodium hydroxide-urea solution offers more competitive raw material costs and processing technology.

[0029] (3) During the directional freezing process, the cellulose gel precursor gradually forms ice crystals during freezing. The ice crystal framework plays a supporting role in the gel structure, reducing gel shrinkage and crack formation. It can maintain the structural integrity and stability of the aerogel, thereby obtaining a directional pore structure, nanoscale pore size distribution and orderly arrangement of microstructure, so that the aerogel has a large specific surface area and porosity.

[0030] (4) Modified nano-zinc oxide adheres to the interior and surface of the cellulose aerogel, increasing the stress-bearing surface when external force is applied, thereby effectively dispersing stress, avoiding stress concentration, and significantly improving the overall compressive strength and rigidity. At the same time, it increases the surface roughness of the aerogel, introduces hydrophobic groups, and reduces the hygroscopicity of the aerogel. Attached Figure Description

[0031] Figure 1 This is a schematic diagram of the directional freezing device used in this invention;

[0032] In the diagram, 1 is a liquid nitrogen container, 2 is liquid nitrogen, 3 is an insulation shell, 4 is a copper column, 5 is a PP tubular mold, and 6 is a mixed solution. A copper column is vertically installed below one end of the PP tubular mold and extends into the liquid nitrogen container. The mold is placed in the liquid nitrogen container, which is located inside the insulation shell. One end of the copper column is placed in the liquid nitrogen, and a temperature gradient is formed on the surface of the circular copper column.

[0033] Figure 2 These are SEM images of the cross sections of the cellulose / nano zinc oxide composite aerogels prepared in Example 1(a) and Comparative Example 1(b);

[0034] Figure 3 These are SEM images of the cross sections of the cellulose / nano zinc oxide composite aerogels prepared in Example 2(a) and Comparative Example 2(b);

[0035] Figure 4 These are the stress-strain curves of the cellulose / nano zinc oxide composite aerogels prepared in Example 2 and Comparative Example 2;

[0036] Figure 5 SEM images of the surfaces of the cellulose / nano zinc oxide composite aerogels prepared in Example 3(a) and Comparative Example 3(b);

[0037] Figure 6 These are polarized light microscope images of the cellulose dissolution state in the solutions of Example 4(a) and Comparative Example 4(b);

[0038] Figure 7 The surface temperature-time curves of the aerogels prepared in Example 3 and Comparative Example 5 are shown.

[0039] Figure 8Infrared thermal imaging images of the aerogels prepared in Example 3 and Comparative Example 5;

[0040] Figure 9 The water contact angle of the aerogels prepared in Example 3(a) and Comparative Example 5(b). Detailed Implementation

[0041] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments:

[0042] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art.

[0043] Mechanical performance testing steps:

[0044] The compressive strength of the composite aerogel was measured using a CTM2050 electronic universal testing machine to evaluate its mechanical properties. A 100mm diameter compression clamp was used to place the composite aerogel sample in the center of the pressure plate, and the test was then initiated. The preload force was set to 0.005N, and the compression rate was 0.5mm / min.

[0045] Thermal insulation performance test steps:

[0046] The thermal insulation performance of the composite aerogel was visualized using a FOTRIC 240M infrared thermal imager. The aerogel was placed in a heat source with a set temperature of 80℃ for 10 minutes, and the temperature change of the aerogel surface was recorded and infrared thermal images were captured.

[0047] Hydrophobicity test procedure:

[0048] The composite aerogel was neatly attached to a glass slide. Using the automatic injection system of the contact angle measuring instrument, 5 μL of liquid was dropped onto the surface of the composite aerogel. The water contact angle was analyzed and the changes in the water contact angle were recorded.

[0049] Example 1

[0050] A method for preparing a cellulose / nano zinc oxide composite aerogel, comprising the following steps:

[0051] (1) Preparation of modified nano-zinc oxide particles: Nano-zinc oxide was added to anhydrous ethanol at a mass ratio of 1:30. A uniform nano-zinc oxide suspension was obtained by ultrasonic treatment and vigorous stirring. γ-methacryloyloxypropyltrimethoxysilane at a mass ratio of 10:1 relative to the nano-zinc oxide was added to the suspension. The mixture was stirred in an oil bath for 10 h at 80 °C. The reaction mixture was ultrasonically centrifuged, the product was collected, washed with anhydrous ethanol, and then dried in an oven to obtain modified nano-zinc oxide particles.

[0052] (2) Preparation of cellulose solution: Sodium hydroxide and urea were added to deionized water and stirred until completely dissolved to form a clear and transparent strongly alkaline solution. Then, the solution was placed in the freezer compartment of a refrigerator (pre-freezing temperature: -18℃) for 3 hours to prepare a pre-cooled alkaline solution containing urea and sodium hydroxide. Cellulose was quickly added to the pre-cooled alkaline solution and stirred evenly at 2℃ for 3 hours to finally obtain a cellulose solution; wherein the mass ratio of sodium hydroxide, urea, water and cellulose was 7:26:67:3.

[0053] (3) Preparation of cellulose / nano zinc oxide mixed solution: Modified nano zinc oxide particles were slowly added to the cellulose solution under stirring. The mass ratio of modified nano zinc oxide particles to cellulose was 1:5. The mixture was stirred evenly to allow it to fully mix and react for 1 hour to obtain the cellulose / nano zinc oxide mixed solution.

[0054] (4) Preparation of cellulose / nano zinc oxide composite hydrogel: The cellulose / nano zinc oxide mixed solution was poured into a directional freezing device. The directional freezing temperature was -196℃ and the time was 20min. After taking it out, it was allowed to stand at room temperature for 8h. The formed gel was exchanged with ethanol to form a hydrogel. Then it was washed with deionized water to remove excess solvent until pH=7, and the cellulose / nano zinc oxide composite hydrogel was obtained.

[0055] (5) Preparation of cellulose / nano zinc oxide composite aerogel: The obtained cellulose / nano zinc oxide composite hydrogel was placed in a freeze dryer, the freeze drying temperature was -55℃, and the drying time was 48h to obtain cellulose / nano zinc oxide composite aerogel.

[0056] Example 2

[0057] A method for preparing a cellulose / nano zinc oxide composite aerogel, comprising the following steps:

[0058] (1) Preparation of modified nano-zinc oxide particles: Nano-zinc oxide was added to anhydrous ethanol at a mass ratio of 1:20. A uniform nano-zinc oxide suspension was obtained by ultrasonic treatment and vigorous stirring. γ-methacryloyloxypropyltrimethoxysilane at a mass ratio of 10:1 relative to the nano-zinc oxide was added to the suspension. The mixture was stirred in an oil bath for 11 h at 90 °C. The reaction mixture was ultrasonically centrifuged, the product was collected, washed with anhydrous ethanol, and then dried in an oven to obtain modified nano-zinc oxide particles.

[0059] (2) Preparation of cellulose solution: Sodium hydroxide and urea were added to deionized water and stirred until completely dissolved to form a clear and transparent strongly alkaline solution. Then, the solution was placed in the freezer compartment of a refrigerator (pre-freezing temperature: -18℃) for 3 hours to prepare a pre-cooled alkaline solution containing urea and sodium hydroxide. Next, cellulose was quickly added to the pre-cooled alkaline solution and stirred evenly at 2℃ for 4 hours to finally obtain a cellulose solution with a mass ratio of sodium hydroxide, urea, water, and cellulose of 7:26:67:3.

[0060] (3) Preparation of cellulose / nano zinc oxide mixed solution: Modified nano zinc oxide particles were slowly added to the cellulose solution under stirring. The mass ratio of modified nano zinc oxide particles to cellulose was 1:5. The mixture was stirred evenly to allow it to fully mix and react for 1 hour to obtain the cellulose / nano zinc oxide mixed solution.

[0061] (4) Preparation of cellulose / nano zinc oxide composite hydrogel: The cellulose / nano zinc oxide mixed solution was poured into a directional freezing device. The directional freezing temperature was -196℃ and the time was 30min. After taking it out, it was allowed to stand at room temperature for 8h. The formed gel was exchanged with ethanol to form a hydrogel. Then it was washed with deionized water to remove excess solvent until pH=7, and the cellulose / nano zinc oxide composite hydrogel was obtained.

[0062] (5) Preparation of cellulose / nano zinc oxide composite aerogel: The obtained cellulose / nano zinc oxide composite hydrogel was placed in a freeze dryer, the freeze drying temperature was -55℃, and the drying time was 48h to obtain cellulose / nano zinc oxide composite aerogel.

[0063] Example 3

[0064] A method for preparing a cellulose / nano zinc oxide composite aerogel, comprising the following steps:

[0065] (1) Preparation of modified nano-zinc oxide particles: Nano-zinc oxide was added to anhydrous ethanol at a mass ratio of 1:30. Ultrasonic treatment and vigorous stirring were used to obtain a uniform nano-zinc oxide suspension. γ-methacryloyloxypropyltrimethoxysilane was added to the suspension at a mass ratio of 20:1 relative to the nano-zinc oxide, and the mixture was stirred in an oil bath for 12 h at 100℃. The reaction mixture was ultrasonically centrifuged, the product was collected, washed with anhydrous ethanol, and then dried in an oven to obtain modified nano-zinc oxide particles.

[0066] (2) Preparation of cellulose solution: Sodium hydroxide and urea were added to deionized water and stirred until completely dissolved to form a clear and transparent strongly alkaline solution. Then, the solution was placed in the freezer compartment of a refrigerator (pre-freezing temperature: -18℃) for 3 hours to prepare a pre-cooled alkaline solution containing urea and sodium hydroxide. Next, cellulose was quickly added to the pre-cooled alkaline solution and stirred evenly at 1℃ for 5 hours to finally obtain a cellulose solution with a mass ratio of sodium hydroxide, urea, water, and cellulose of 7:26:67:3.

[0067] (3) Preparation of cellulose / nano zinc oxide mixed solution: Modified nano zinc oxide particles were slowly added to the cellulose solution under stirring. The mass ratio of modified nano zinc oxide particles to cellulose was 1:10. The mixture was stirred evenly to allow it to fully mix and react for 1 hour to obtain the cellulose / nano zinc oxide mixed solution.

[0068] (4) Preparation of cellulose / nano zinc oxide composite hydrogel: The cellulose / nano zinc oxide mixed solution was poured into a directional freezing device. The directional freezing temperature was -196℃ and the time was 30min. After taking it out, it was left to stand at room temperature for 6h to exchange the formed gel with ethanol to form a hydrogel. Then it was washed with deionized water to remove excess solvent until pH=7, and the cellulose / nano zinc oxide composite hydrogel was obtained.

[0069] (5) Preparation of cellulose / nano zinc oxide composite aerogel: The obtained cellulose / nano zinc oxide composite hydrogel was placed in a freeze dryer, the freeze drying temperature was -55℃, and the drying time was 48h to obtain cellulose / nano zinc oxide composite aerogel.

[0070] Example 4

[0071] A method for preparing a cellulose / nano zinc oxide composite aerogel, comprising the following steps:

[0072] (1) Preparation of modified nano-zinc oxide particles: Nano-zinc oxide was added to anhydrous ethanol at a mass ratio of 1:30. Ultrasonic treatment and vigorous stirring were used to obtain a uniform nano-zinc oxide suspension. γ-methacryloyloxypropyltrimethoxysilane was added to the suspension at a mass ratio of 20:1 relative to the nano-zinc oxide. The mixture was stirred in an oil bath for 10 h at 100℃. The reaction mixture was ultrasonically centrifuged, the product was collected, washed with anhydrous ethanol, and then dried in an oven to obtain modified nano-zinc oxide particles.

[0073] (2) Preparation of cellulose solution: Sodium hydroxide and urea were added to deionized water and stirred until completely dissolved to form a clear and transparent strongly alkaline solution. Then, the solution was placed in the freezer compartment of a refrigerator (pre-freezing temperature: -18℃) for 3 hours to prepare a pre-cooled alkaline solution containing urea and sodium hydroxide. Next, cellulose was quickly added to the pre-cooled alkaline solution and stirred evenly at 1℃ for 4 hours to finally obtain a cellulose solution with a mass ratio of sodium hydroxide, urea, water, and cellulose of 7:26:67:3.

[0074] (3) Preparation of cellulose / nano zinc oxide mixed solution: Modified nano zinc oxide particles were slowly added to the cellulose solution under stirring. The mass ratio of modified nano zinc oxide particles to cellulose was 1:10. The mixture was stirred evenly to allow it to fully mix and react for 1 hour to obtain cellulose / nano zinc oxide mixed solution.

[0075] (4) Preparation of cellulose / nano zinc oxide composite hydrogel: The cellulose / nano zinc oxide mixed solution was poured into a directional freezing device. The directional freezing temperature was -196℃ and the time was 20min. After taking it out, it was left to stand at room temperature for 7h to exchange the formed gel with ethanol to form a hydrogel. Then, it was washed with deionized water to remove excess solvent until pH=7, and the cellulose / nano zinc oxide composite hydrogel was obtained.

[0076] (5) Preparation of cellulose / nano zinc oxide composite aerogel: The obtained cellulose / nano zinc oxide composite hydrogel was placed in a freeze dryer, the freeze drying temperature was -55℃, and the drying time was 48h to obtain cellulose / nano zinc oxide composite aerogel.

[0077] Comparative Example 1

[0078] The preparation method is the same as in Example 1, except that in step (2), the mass ratio of sodium hydroxide, urea, water and cellulose is 7:26:67:2.

[0079] Figure 2These are SEM images of the cross-sections of the cellulose / nano zinc oxide composite aerogels prepared in Example 1(a) and Comparative Example 1(b). The cross-section of the cellulose / nano zinc oxide composite aerogel prepared in Example 1 (cellulose content of 3%) exhibits a dense and uniform pore structure, while the cross-section of the cellulose / nano zinc oxide composite aerogel prepared in Comparative Example 1 (cellulose content of 2%) has a relatively loose and irregular porous structure. This is because the lower cellulose content reduces the strength of the gel skeleton, leading to the collapse of some pore structures.

[0080] Comparative Example 2

[0081] The preparation method is the same as in Example 2, except that in step (4), the cellulose / nano zinc oxide mixed solution is directly placed in the refrigerator to freeze (temperature is -12℃, time is 12h), and after taking it out, it is left to stand at room temperature for 8h. The formed gel is exchanged with ethanol to form a hydrogel, and then washed with deionized water to remove excess solvent until pH=7, to obtain cellulose / nano zinc oxide composite hydrogel.

[0082] Figure 3 These are SEM images of the cross-sections of the cellulose / nano zinc oxide composite aerogels prepared in Example 2(a) and Comparative Example 2(b). The cellulose / nano zinc oxide composite aerogel prepared in Example 2 (directional freezing) exhibits a uniform and ordered three-dimensional layered porous structure, with layers interconnected by fibrous substructures. The directional freezing process guided the growth direction of ice crystals, resulting in a directional pore structure formed by cellulose and nano zinc oxide after freeze-drying. This enhances the overall strength and stability of the aerogel. In contrast, the cellulose / nano zinc oxide composite aerogel prepared in Comparative Example 2 (direct freezing) showed no directionality in ice crystal formation during direct freezing, resulting in a random, porous microstructure. This structure lacks layered arrangement and has uneven pore size, leading to a loose structure.

[0083] Figure 4 These are the stress-strain curves of the cellulose / nano zinc oxide composite aerogels prepared in Example 2 and Comparative Example 2. Compared to the cellulose / nano zinc oxide composite aerogel prepared in Comparative Example 2, Example 2 exhibits higher compressive strength. This is mainly attributed to the stable and dense three-dimensional network structure formed by cellulose through hydrogen bonding, which enhances the overall strength of the aerogel. Furthermore, the multilayer porous structure of the aerogel endows it with excellent damping properties. When external force is applied to the composite aerogel, this multilayer structure can effectively dissipate the external force layer by layer along the pore path.

[0084] Comparative Example 3

[0085] The preparation method is the same as in Example 3, except that step (1) is omitted and no modification treatment is performed on the nano zinc oxide. In step (3), nano zinc oxide particles are slowly added to the cellulose solution under stirring. The mass ratio of nano zinc oxide particles to cellulose is 1:10. At the same time, the mixture is stirred evenly to allow it to fully mix and react for 1 hour to obtain a cellulose / nano zinc oxide mixed solution.

[0086] Figure 5 SEM images of the surfaces of the cellulose / nano zinc oxide composite aerogels prepared in Example 3(a) and Comparative Example 3(b); the nano zinc oxide on the surface of Example 3 (modified nano zinc oxide) exhibits uniform dispersion and small particle size. The nano zinc oxide on the surface of Comparative Example 3 (nano zinc oxide) has a larger particle size, exhibits clustered aggregation, and is unevenly distributed. After modification, an organic coating gradually forms on the zinc oxide surface, significantly reducing the tendency for particle aggregation and greatly improving its dispersibility in the matrix.

[0087] Comparative Example 4

[0088] The preparation method is the same as in Example 4, except that in step (2), the pre-freezing and continuous low-temperature stirring process is omitted during the cellulose dissolution process. The cellulose is directly added to the prepared sodium hydroxide-urea solution to obtain a cellulose solution. The mass ratio of sodium hydroxide, urea, water and cellulose is 7:26:67:3.

[0089] Figure 6 These are polarized light microscope images of the cellulose dissolution state in the solutions of Example 4(a) and Comparative Example 4(b). Example 4 (pre-freezing + continuous low-temperature stirring) significantly promoted the dissolution of cellulose in sodium hydroxide and urea solutions. At 0 h, neither solution had dissolved. After 2 h, most of the cellulose in Example 4 had dissolved, while only a small portion of the cellulose in Comparative Example 4 had dissolved. After 4 h, the cellulose in Example 4 was almost completely dissolved, while the cellulose in Comparative Example 4 was still not completely dissolved. This indicates that freezing and continuous low-temperature stirring significantly promoted the dissolution of cellulose in sodium hydroxide and urea solutions, resulting in almost complete dissolution of cellulose in a short time. Without these treatments, the degree of cellulose dissolution was lower, and the dissolution effect was significantly less than that in Example 4.

[0090] Comparative Example 5

[0091] A method for preparing cellulose aerogel, comprising the following steps:

[0092] The difference from Example 3 above is that no nano zinc oxide particles are added.

[0093] (1) Preparation of cellulose solution: Sodium hydroxide and urea were added to deionized water and stirred until completely dissolved to form a clear and transparent strongly alkaline solution. Then, the solution was placed in the freezer compartment of a refrigerator (pre-freezing temperature: -18℃) for 3 hours to prepare a pre-cooled alkaline solution containing urea and sodium hydroxide. Next, cellulose was quickly added to the pre-cooled alkaline solution and stirred evenly at 1℃ for 5 hours to finally obtain a cellulose solution with a mass ratio of sodium hydroxide, urea, water and cellulose of 7:26:67:3.

[0094] (2) Preparation of cellulose hydrogel: The cellulose solution was poured into a directional freezing device, the directional freezing temperature was -190℃ and the time was 30min. After taking it out, it was left to stand at room temperature for 6h to exchange the formed gel with ethanol to form a hydrogel. Then it was washed with deionized water to remove excess solvent until pH=7, and the cellulose hydrogel was obtained.

[0095] (3) Preparation of cellulose aerogel: The obtained cellulose hydrogel was placed in a freeze dryer and the freeze drying temperature was -55℃ for 48h to obtain cellulose aerogel.

[0096] Figure 7 The surface temperature-time curves for the aerogels prepared in Example 3 and Comparative Example 5 are shown. In the initial 0-30 seconds, the surface temperature of the aerogel rapidly increases, then gradually stabilizes, eventually reaching thermal equilibrium. The final stable temperature of the cellulose aerogel prepared in Comparative Example 5 is significantly higher than that of the composite aerogel prepared in Example 3, which is loaded with nano-zinc oxide and prepared under the same cellulose content conditions. The composite aerogel prepared in Example 3 exhibits superior thermal insulation performance.

[0097] Figure 8 Infrared thermal imaging images of the aerogels prepared in Example 3 and Comparative Example 5 are shown. The infrared thermal imaging further reveals a significant difference in thermal insulation performance between the aerogel of Comparative Example 5 and the aerogel of Example 3. The heat source covered by the aerogel exhibits a clear color difference in the imaging. Specifically, the color change rate of the area covered by the aerogel of Example 3 is slower, indicating a more significant thermal insulation effect and a significantly longer thermal insulation time.

[0098] Figure 9 The water contact angles are shown for the aerogels prepared in Example 3(a) and Comparative Example 5(b). The cellulose / nano zinc oxide composite aerogel prepared in Example 3 has a contact angle exceeding 120°, with water droplets forming spherical shapes, exhibiting strong hydrophobicity. This indicates that the aerogel surface of Example 3 has good hydrophobic properties, while the cellulose aerogel prepared in Comparative Example 5 has a contact angle close to 0°, with water droplets completely spreading on the aerogel surface, exhibiting strong hydrophilicity. Modified nano zinc oxide increases the surface roughness of the aerogel, introduces hydrophobic groups, reduces the hygroscopicity of the aerogel, and thus exhibits good hydrophobic properties.

[0099] The embodiments provided above are not intended to limit the scope of the invention, nor are the described steps intended to limit the order of execution. Any obvious modifications made to the invention by those skilled in the art based on existing common knowledge also fall within the scope of protection defined by the claims.

Claims

1. A method for preparing cellulose / nano zinc oxide composite aerogel, characterized in that: The steps include: (1) adding anhydrous ethanol to nano zinc oxide for ultrasonic treatment, then adding γ-methacryloxypropyltrimethoxysilane for reaction, and finally centrifuging, washing, and drying to obtain modified nano zinc oxide particles; (2) adding sodium hydroxide and urea to water, stirring until dissolved, and then pre-freezing to obtain a pre-cooled alkali solution, and then adding cellulose to the pre-cooled alkali solution to react and obtain a cellulose solution; (3) adding the modified nano zinc oxide particles to the cellulose solution to obtain a cellulose / nano zinc oxide mixed solution, placing the cellulose / nano zinc oxide mixed solution in a directional freezing device for treatment, taking it out for standing, washing, and obtaining a cellulose / nano zinc oxide composite hydrogel; (4) The cellulose / nano-zinc oxide composite hydrogel is freeze-dried to obtain a cellulose / nano-zinc oxide composite aerogel.

2. The method for preparing a cellulose / nano zinc oxide composite aerogel according to claim 1, characterized in that: In step (1), the mass ratio of nano zinc oxide to anhydrous ethanol is 1:20-30.

3. The method for preparing a cellulose / nano zinc oxide composite aerogel according to claim 1, characterized in that: In step (1), the mass ratio of nano zinc oxide to γ-methacryloxypropyltrimethoxysilane is 10-20:1; the reaction temperature is 80-100° C., and the reaction time is 10-12 h.

4. The method for preparing a cellulose / nano zinc oxide composite aerogel according to claim 1, characterized in that: In step (2), the mass ratio of sodium hydroxide, urea, water and cellulose is 7:26:67:

3.

5. The method for preparing a cellulose / nano zinc oxide composite aerogel according to claim 1, characterized in that: In step (2), the pre-freezing temperature is -18--12°C, and the pre-freezing time is 3-5h.

6. The method for preparing a cellulose / nano zinc oxide composite aerogel according to claim 1, characterized in that: In step (2), cellulose is added to the pre-cooled alkali solution and stirred to react at 1-3° C. for 3-5 hours.

7. The method for preparing a cellulose / nano zinc oxide composite aerogel according to claim 1, characterized in that: In step (3), the mass ratio of modified nano zinc oxide particles to cellulose is 1:(5-10).

8. The method for preparing a cellulose / nano zinc oxide composite aerogel according to claim 1, characterized in that: In step (3), the temperature of directional freezing is -196°C and the time is 20-30 minutes.

9. The cellulose / nano zinc oxide composite aerogel prepared by the method according to any one of claims 1 to 8.

10. Use of the cellulose / nano zinc oxide composite aerogel according to claim 9 in the field of thermal insulation materials.

Citation Information

Patent Citations

  • Method for preparing cellulose composite aerogel

    CN102443180A

  • Novel gas-sensitive aerogel material and preparation method thereof

    CN106397792A

  • Chestnut shell aerogel as well as preparation method and application thereof

    CN112791010A

  • Flexible hydrophobic anisotropic cellulose nanofiber aerogel phase-change composite material and preparation method thereof

    CN114032071A

  • Preparation method of microcrystalline cellulose / Al2O3-SiO2 composite aerogel

    CN116003870A